Effects of a lipid-encapsulated zinc oxide supplement on growth performance and intestinal morphology and digestive enzyme activities in weanling pigs - Jang, Insurk (J Anim Sci Technol, 2014)
This study compared the effects of varying lipid content and dietary concentration of a lipid-encapsulated (LE) ZnO product to those of native ZnO and thereby to find insights into optimal lipid coating and dosage of the Zn supplement. A total of 192 21-d-old weanling pigs were allotted to 48 pens, after which each six pens received a ZnO-free basal diet supplemented with 125 ppm ZnO (100 ppm Zn; BASAL), 2,500 ppm Zn as native ZnO (HIGH), or 100 or 200 ppm Zn as LE ZnO (LE-100 or LE-250) containing 8%, 10%, or 12% lipid [LE-8%, LE-10%, or LE-12%, respectively; 2 × 3 factorial arrangement within the LE-ZnO diets (LE-ALL)] for 14 d. Forty pigs were killed at the end for histological and biochemical examinations. None of ADG, ADFI, gain:feed, and fecal consistency score differed between the LE-ALL and either of the BASAL and HIGH groups. Hepatic and serum Zn concentrations were greater (p <0.05) in the HIGH vs. LE-ALL group, but did not differ between LE-ALL and BASAL, between LE-100 and -250, or among LE-8%, -10%, and -12% groups. Villus height (VH), crypt depth (CD), and the VH:CD ratio in the duodenum, jejunum, and ileum did not differ between the LE-ALL and either of the BASAL and HIGH groups, except for a greater CD in the duodenum in the LE-ALL vs. HIGH group. Additionally, VH and CD in the duodenum and VH:CD in the jejunum were greater in the LE-250 vs. LE-100 group. Specific activities of sucrase, maltase, and leucine aminopeptidase in these intestinal regions and those of amylase and trypsin in the pancreas were not influenced by the lipid content or dietary concentration of LE ZnO and also did not differ between the LE-ALL and either of the BASAL and HIGH groups, except for a greater pancreatic amylase activity in the former vs. HIGH group. In conclusion, the present results indicate that the LE ZnO, regardless of its lipid percentage or supplementation level examined in this study, has no significant effect on growth performance, fecal consistency, or digestive enzyme activities of weanling pigs under the experimental conditions.